For an actantial model of the body in metamorphosis in horror film - Silva Odair José Moreira da (Estudos Semióticos, 2013)
There is no escaping the assertion that horror cinema postulates the hardships of fear in grotesque representation of the body. A subgenre of this type which emerges is the body horror, wherein the effect of sense of fear arises from the construction of a monstrous-horrendous body, whose identity was previously figurative designed as a model actancial body in metamorphosis. As a reference center of the flesh, the metamorphosis is grounded on four forces that generate pressures and impulses on the body-actant of the subject in construction, limiting it to a specific body system. These forces affect the body-actant and protrude out of his self reference, as it postulates the reverse as a new way of life. The subject is the reverse of the anti-subject horizon towards the grotesque. Projection of bodies in the filmic narrative, we can say that the body has characteristics disturbing horror, both design of bodies-actants immersed in fear and perception of a body that sets the discomfort of the supernatural as a grotesque form of spill over the anxieties of the world. Therefore, it is postulated here a model actancial body in metamorphosis, established in the statement of horror from four forces that shape a system body guiding the development of the narratives of fear: the modification, the transformation, the transmutation, and the mutation.